Efektivitas Penyampaian Relaas Panggilan Sidang melalui Surat Tercatat di Pengadilan Agama Pangkajene - Fahmiah Asaf; Basri, Rusdaya; Rahmawati; L, Sudirman; Saidah (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2026)
The lawful and proper service of court summonses is essential to safeguarding the parties’ rights and ensuring the validity of judicial proceedings. This study aims to analyze the legal mechanism and procedure for serving court summonses by registered mail at the Pangkajene Religious Court and to identify the factors supporting and hindering its effectiveness. This research is a field study employing an empirical juridical approach and a descriptive qualitative method. The data consist of primary data obtained through interviews and observations, as well as secondary data derived from legislation, court documents, and relevant literature. Data were collected through interviews, observation, and documentation and were analyzed through data reduction, data presentation, and conclusion drawing using the perspectives of legal effectiveness, public service, and legal certainty. The findings indicate that the service of court summonses by registered mail has a clear legal basis and has been implemented in accordance with the principles of lawful and proper summonses under civil procedural law. The procedure has been carried out systematically, beginning with the determination of the hearing date, preparation of the summons by the bailiff, delivery through a postal service provider, and administration of proof of receipt. The use of registered mail provides several benefits, including legal validity, traceability, time efficiency, and reduced service costs. However, its empirical effectiveness remains affected by inaccurate addresses, delivery delays, geographical conditions, limited efforts to trace recipients, and suboptimal coordination among the court, postal service provider, and local authorities.